Phylogenetic Reassessment, Taxonomy, and Biogeography of Codinaea and Similar Fungi - Martina Réblová; Miroslav Kolařík; Jana Nekvindová; Kamila Réblová; František Sklenář; Andrew N. Miller; Margarita Hernández-Restrepo (Journal of Fungi, 2021)
The genus Codinaea is a phialidic, dematiaceous hyphomycete known for its intriguing morphology and turbulent taxonomic history. This polyphasic study represents a new, comprehensive view on the taxonomy, systematics, and biogeography of Codinaea and its relatives. Phylogenetic analyses of three nuclear loci confirmed that Codinaea is polyphyletic. The generic concept was emended; it includes four morphotypes that contribute to its morphological complexity. Ancestral inference showed that the evolution of some traits is correlated and that these traits previously used to delimit taxa at the generic level occur in species that were shown to be congeneric. Five lineages of Codinaea-like fungi were recognized and introduced as new genera: Codinaeella, Nimesporella, Stilbochaeta, Tainosphaeriella, and Xyladelphia. Dual DNA barcoding facilitated identification at the species level. Codinaea and its segregates thrive on decaying plants, rarely occurring as endophytes or plant pathogens. Environmental ITS sequences indicate that they are common in bulk soil. The geographic distribution found using GlobalFungi database was consistent with known data. Most species are distributed in either the Holarctic realm or tropical geographic regions. The ancestral climatic zone was temperate, followed by transitions to the tropics; these fungi evolved primarily in Eurasia and Americas, with subsequent transitions to Africa and Australasia.